Enhancing Company Value in Islamic Banking: The Interplay of Corporate Social Responsibility and Financial Performance - Andi Triyawan; Suryawiastarani; Adamu Abubakar Muhammad (Universitas Pembangunan Nasional Veteran Jakarta, 2025)
Corporate Social Responsibility (CSR) is a crucial factor influencing firm value, significantly impacting profitability, corporate valuation, and financial performance across various sectors. The relationship between CSR, financial performance, and firm value often follows a U-shaped pattern, where initial CSR investments may incur costs but lead to greater long-term benefits through enhanced stakeholder trust. In Sharia-compliant financial institutions, the integration of CSR governance is increasingly important due to evolving market expectations. This study investigates the effects of CSR and financial performance on firm value in Sharia-compliant banks listed on the JII70 index from 2020 to 2023. Using a quantitative descriptive design, the research analyzes a purposive sample of three Islamic banks over four years, utilizing secondary data from annual reports and sustainability disclosures. The findings reveal that CSR and financial performance together explain 78% of the variation in firm value, underscoring the importance of robust CSR implementation for optimizing firm valuation. CSR and FP don't affect company value much separately. However, they are significant affect when combined (F-test). Tanggung Jawab Sosial Perusahaan (CSR) memiliki peran penting dalam membentuk nilai perusahaan, terutama pada lembaga keuangan syariah yang menekankan aspek etika dan sosial. Penelitian ini bertujuan untuk menganalisis pengaruh CSR dan kinerja keuangan terhadap nilai perusahaan pada bank syariah yang terdaftar dalam indeks JII70 selama periode 2020–2023. Metode yang digunakan adalah deskriptif kuantitatif dengan menganalisis data sekunder dari laporan tahunan dan laporan keberlanjutan tiga bank syariah terpilih. Hasil penelitian menunjukkan bahwa CSR dan kinerja keuangan secara bersama-sama mampu menjelaskan 78% variasi nilai perusahaan. Temuan ini menunjukkan bahwa penerapan CSR yang kuat, didukung kinerja keuangan yang baik, secara signifikan dapat meningkatkan valuasi perusahaan. Studi ini menegaskan pentingnya integrasi CSR dalam manajemen strategis, khususnya bagi institusi keuangan syariah yang ingin memperkuat kepercayaan pemangku kepentingan dan pertumbuhan jangka panjang. CSR dan FP tidak banyak memengaruhi nilai perusahaan secara terpisah. Namun, keduanya mempengaruhi valuasi perusahaan ketika digabungkan (uji F).